Role of Healthcare Staff in Promoting Mental Health & Wellbeing in Community - JAMAL SIDDIQUI, SARMAD; SAIFULLAH JAMRO, FAISAL; AHMED, SHAHID; RAM, DAULAT; ALI SHAIKH, ZAHID; LAL PRITHIANI, SHAM (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In many low- and middle-income nations, including Pakistan, where data on the frequency of mental health disorders is lacking, mental health is an underappreciated field. This issue is made worse by the unequal distribution of mental health service providers as well as the general public’s pervasive ignorance and stigma about mental illness. Objective: The purpose of the study conducted in Larkana, Sindh, Pakistan, was to evaluate community members’ and healthcare professionals’ knowledge, attitudes, and practices around mental health. Methods: 540 people of the community and 110 healthcare professionals participated in the descriptive cross-sectional survey, which included qualitative and quantitative approaches. Key informant interviews, focus groups, and household surveys were used to gather data, which was then analyzed using thematic analysis, descriptive statistics, and univariate frequencies. Results: According to the survey, 68% of healthcare workers had been diagnosed with mental health disorders, whilst 39% of community members had a family member with a mental health issue. Substance misuse, heredity, spiritual origins, and socioeconomic pressures were frequently cited as reasons for mental disease. Just 29.4% of HCWs reported that counseling services were available at health facilities, indicating a large gap in this regard. Between health care workers and members of the community, opinions on how accessible and affordable mental health services are varied significantly. Furthermore, although healthcare workers indicated that free medication was available, community members reported shortages. The study also emphasized the usage of traditional healers and religious leaders for mental health issues and observed differences in attitudes toward patients with mental illness in terms of respect and dignity. Conclusion: With its emphasis on the high prevalence of mental illness, the scarcity of resources, and the pervasive myths and misconceptions, this study offers insightful information about the state of mental health in Larkana, Pakistan. In order to effectively treat mental health issues in Pakistan and other comparable rural contexts, it emphasizes the need for stronger health systems, increased public awareness, and better training for healthcare workers.